"Dormant Shell, " With Plan, Held to Meet Operational Test. Issue 2 (February 2015) - Unknown
<x xml:space="preserve">Abstract</x> A charitable organization, with no assets and current operations, was held eligible for continuing tax exemption because of its plan to resume operations at some later, undefined point in time (Priv. Ltr. Rul. 201448026).